Do Oil Prices Govern GDP and Public Spending Avenues in Saudi Arabia? Sensitivity and Trend Analysis - Ali, Anis (International Journal of Energy Economics and Policy, 2021)
The oil revenue constitutes 50% of the GDP of Saudi Arabia approximately and indirectly governs the Public spending Avenues (PSA). The study finds out the symmetry in sensitivity and trend of Oil prices (OP), GDP, and Public Spending Avenues (PSA) and the impact of volatility of oil prices on the GDP, and PSA. The analysis is based on the Chain based Index (CBI) and Fixed Based Index (FBI) numbers to get the sensitivity and trend movement of the variables. Coefficient of variations (CV), ANOVA (Analysis of Variance), and correlation computed to get normality, similarity, and the casual relationship of the variables. OP governs the GDP positively and proportionately while there is a negative correlation between the OP variations and the PSA. Saudi Arabian government enhances its spending on PSA and especially on education irrespective of the lowering of OP year by year. OP and GDP do not govern the movement trend of PSA in the long term while shocks of OP and GDP yearly affect the PSA of Saudi Arabia. There is a need to diversify the income resources to minimize the dependency on OP and hedging the budget deficit from the volatility of OP by considering the impact of the sensitivity of OP on the economy and PSA. The policymakers must consider the sensitivity, trend, and governance of GDP and PSA by the OP to formulate the appropriate policies to shift oil economy to non-oil economy to minimize the impact of shocks of OP on the economy. Keywords: Oil prices, Public spending, oil sector revenue, Saudi Arabia, optional resources. JEL Classifications: Q40, Q41, I10, I20, I30 DOI: https://doi.org/10.32479/ijeep.10791